Hubungan Antara Menyusui Dengan Involusi Uterus Pada Ibu Nifas Fisiologis Di RSIA Aura Syifa Kabupaten Kediri - Eny Sendra; Dewi Indriani (Akademi Keperawatan Dharma Husada Kediri, 2017)
Breast feeding is giving milk to be drunk to the baby from the breast. Uterus involution is a process how the uterus return to the condition back, before pregnanting after bearing. At the moment of suckling, happens a stimulus and brings the hormones out, such as oksitosin uses not only to stimulate some muscles constraction but also to stimulate the uterus, so that the process of uterus involution happens foster. According to the explanations above, the research aimed to know about the correlation between breast feeding and uterus involution. This research’s design was, cross sectional by the population of all childbirth mothers approximately 50 persons / month. By using accidental sampling technique we got 21 sample respondents. The place of research in RSIA Aura Syifa in Kediri Regency on 16th until 22nd of June 2009. From this research’s result, we got 14 persons (66,67%) with normal uterus involution, suckled in a good way, one person (4,67%) with normal uterus involution, suckled in a wrong way, 2 persons (9,52%) with abnormal uterus involution, suckled in a good way and 4 persons (19,05%) with abnormal uterus involution, suckled in a wrong way. Statistic test which used chi-square test, counted the probability frequency in advance, from that we got 3 columns with the score, less than 5, so that chi-square can not be continued and by doing exact fisher test, the score was 0,001. Because P with the grade mistake 0,05 smaller, so the conclusion was “Ho” is rejected, it meant “there was correlation between suckling and uterus involution”. Key Word : Breast feeding, uterus involution